P.086 Endoscopic assisted ulnar nerve decompression: a technical note. (2nd June 2017) - Alotaibi, MB; Yarascavitch, B; Reddy, K
Abstract : Background: Cubital tunnel syndrome is the second most frequent upper extremity entrapment neuropathy. Various surgical approaches have been described in the literature for Ulnar nerve decompression, ranging from open In-situ decompression to endoscopic Ulnar nerve release. In this technical note we describe a new endoscopic approach for Ulnar nerve decompression.Methods: Four cadavers, a total of eight fresh arms were dissected using our new endoscopic technique. The technique involves a 2.5cm skin incision placed 2.5cm distal to the medial epicondyle, and perpendicular to the long nerve axis. Early identification of motor branches was achieved using this skin incision. Under endoscopic view using 30 degree rigid scope Ulnar nerves were decompressedResults: Early identification of motor branches was achieved using distally placed skin incision in all eight arms.Conclusions: The safety of identifying Ulnar nerve motor branches in the early steps of the procedure, and the avoidance of scar formation over the elbow joint are the proposed advantages of this approach. More clinical studies needed to validate this outcome.